Пріоритетні напрями розвитку фінансово-економічного механізму управління водними ресурсами - Мандзик, В.М. (Економіка природокористування і охорони довкілля, 2013)
У статті проаналізовано структуру фінансового механізму управління водними ресурсами та запропоновано пріоритетні напрями його розвитку за допомогою сучасних інструментів фінансового забезпечення. The study analyzed the structure of the financial mechanism of water management. Established a financial mechanism of water management based on the combination of two basic methods: public financial management (planning management system, which is based on the administrative-command methods of management of financial flows) and financial security (is to apply a wide range of market economic management of finances such as self-financing (equity, mutual and other forms of capital), loans, external loans, etc.). Determined that the mechanism of financial support water complex underdeveloped in comparison with European countries, resulting in water resources of Ukraine is not capitalized. Proposed priorities of the financial mechanism of water management.